Politik Hukum Pengaturan Amandemen Undang-Undang Dasar Negara Kesatuan Republik Indonesia Tahun 1945 - Nuraika Ishak (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2016)
The results showed that an amendment to the 1945 constitution can be categorized as one ofthe ways to realize democracy based on law. That the state of law and democracy are two differentconcepts of freedom. Amendments to the Constitution of 1945 NRI is a form of legal reform andalso a manifestation of the democratic state that aims to benefit the people at large. Political power iscrucial because it is a legitimacy for the authorities to be able to apply the rules. The relationshipbetween politics and law is a relationship that can not be separated. Legal and real politics as asubsystem of society is to be open, because it both affects and is affected olehsubsistem each other aswell as by the social system as a whole. Although the law and politics has the function andjustification are different, but the two are not contradictory. Law and politics contribute according totheir function to drive the social system as a whole. Political law used as instruments to be able tocontrol the running of the government.